CRISPR made easy in human and murine hematopoietic precursors - Hacken, Elisa ten; Gruber, Michaela (Translational Cancer Research, 2017)
The CRISPR/Cas9 technology has revolutionized gene-editing approaches, by favoring rapid and efficient modifications of gene function, from knock-out to knock-in, and even to silencing or activation of target genes (1,2). In the October 25th issue of Cell Reports, Gundry et al. (3) describe a novel and efficient method to engineer hematopoietic stem/progenitor cells (HSPCs), of both human and murine origin. In this study, highly efficient disruption of critical genes for myeloid cell development and function, including Dnmt3a , Eed and Suz12 (4), was achieved through virus-free systems. The authors achieve efficient delivery of small guide RNAs (sgRNAs) to murine Cas9-expressing HSPCs by electroporation, with subsequent knock-out of target genes, while maintaining cell viability and colony-forming properties of the edited cells. Targeting of Eed and Suz12 increased proliferation of the edited cells, and their capacity to serially replate, confirming the oncogenic properties of the gene targets. Importantly, the authors report complete virus-free delivery of both Cas9 and sgRNA in human primary T cells and in cord-blood derived HSPCs. By optimizing culture and transfection protocols they could achieve targeting efficiencies of over 80% in these cells. Off-target effects of the sgRNAs were detectable at a very low rate, while multilineage reconstitution capacity of stem cells was maintained.